2021
DOI: 10.1002/cphc.202100222
|View full text |Cite
|
Sign up to set email alerts
|

Topology Effects in Molecular Organic Electronic Materials: Pyrene and Azupyrene**

Abstract: Pyrene derivatives play a prominent role in organic electronic devices, including field effect transistors, light emitting diodes, and solar cells. The flexibility in the desired properties has previously been achieved by variation of substituents at the periphery of the pyrene backbone. In contrast, the influence of the topology of the central -electron system on the relevant properties such as the band gap or the fluorescence behavior has not yet been addressed. In this work, pyrene is compared with its str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…The multilayer spectra, which probe molecules not in direct contact with the metal surface, are similar for both molecules. The minor differences in the peak shapes with the slight asymmetry of the azupyrene spectrum have been explained by the different molecular topologies . The monolayer spectra of the two molecules show much larger differences, indicating their different interaction with the metal surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The multilayer spectra, which probe molecules not in direct contact with the metal surface, are similar for both molecules. The minor differences in the peak shapes with the slight asymmetry of the azupyrene spectrum have been explained by the different molecular topologies . The monolayer spectra of the two molecules show much larger differences, indicating their different interaction with the metal surface.…”
Section: Resultsmentioning
confidence: 99%
“…The S–W defect was chosen because it is a prototypical and ubiquitous intrinsic point defect of graphene and carbon nanotubes. As a reference representing the topology of regular graphene, we use the benzenoid isomer of azupyrene, pyrene, which consists only of 6-membered rings (6-6-6-6 topology). In contrast, the 5-7-5-7 topology of azupyrene is classified as nonalternant and is known to strongly influence its electronic structure. , In related previous work, we compared the two-ring nonbenzenoid aromatic hydrocarbon azulene (5-7 topology) to its benzenoid isomer naphthalene (6-6 topology) regarding their interaction with Cu(111), Ag(111), and Pt(111) surfaces and found that the former binds stronger to all three surfaces. Considering the structural analogy, we therefore proposed that nonbenzenoid defect sites in graphene may induce enhanced graphene/metal interactions. However, these previous studies were lacking in two essential points: First, the azulene motif rarely occurs as isolated defect, and thus azulene is not a representative model system.…”
mentioning
confidence: 99%
“…The precursors containing ketone structures (38 and 44) were obtained in a reaction sequence that included several main steps, such as nucleophilic addition, reduction, and cyclization. The treatment of precursors with reducing agents and then aromatization under high temperature afforded the final fully conjugated, red, platelike molecules (39) and black needle-like molecules (44). Interestingly, compound 39 exhibited a clear blueshift in the absorption spectrum compared to that of compound 5, which had a smaller conjugated network.…”
Section: Synthesis Of Nonalternant Molecules Containing 5-7 Paired De...mentioning
confidence: 99%
“…Azupyrene exhibits distinctive electronic properties compared to those of its alternant isomer pyrene owing to its nonhexagonal rings, such as smaller energy gap, more localized charge distribution, and a different conjugation pathway. [ 39 ] Furthermore, a modified synthetic procedure was developed by Anderson [ 40 , 41 ] and Jutz, [ 42 ] affording the product in moderate yield, and detailed studies involving theoretical calculations [ 43 , 44 , 45 ] and photochemical spectroscopies [ 39 ] elucidated the influence of the topological structure on the electronic configuration and molecular properties.…”
Section: Synthesis Of Nonalternant Molecules Containing 5–7 Paired De...mentioning
confidence: 99%
“…3 First principles simulation of core level spectroscopy has proved to be an effective tool to disentangle complex overlapping XP signatures of hybrid organic-inorganic interfaces for both monolayer 4 and multilayer thin films. 5 Recent example studies where core-level simulation was vital for the interpretation of experimental spectra include oxygen species on Pt(111), 6 and Porphin on Ag(111) and Cu(111) 7 . Klein et al have shown in a series of recent joint experimental and computational studies how XPS and Near-Edge X-ray Absorption Spectroscopy (NEXAFS) provide evidence for the differences in surface chemical bonding between Naphthalene (Nt) and its topological isomer Azulene (Az) adsorbed on Ag(111), Cu(111) and Pt(111) surfaces.…”
Section: Introductionmentioning
confidence: 99%